Influência do teor e efeito promotor de Ag, Fe, Pd e Pt ao catalisador Ni/CeZrO2 nas reações de oxidação parcial e reforma autotérmica do metano - Dantas, Sandra Cristina (2007)
In the present study the behavior of Ni/CeZrO2 catalysts were investigated for the autothermal reforming and partial oxidation of methane and compared with the sample 10%Ni/Al2O3. Samples with 1.5; 5 and 10% nickel were supported on CeZrO2 and catalysts 10%Ni/CeZrO2 promoted by different metals (Ag, Fe, Pd and Pt). The catalysts were characterized by BET surface area, X-ray diffraction (XRD), temperature-programmed reduction (TPR) and CO2 temperature-programmed desorption (CO2-TPD). BET results showed that the sample supported on alumina presented the highest value of surface area and that the addition of promoters by co-impregnation technique did not affect significantly the values of surface area. XRD analysis showed the formation of a ceria-zirconia solid solution. TPR profiles showed the presence of different interactions between nickel and the support. It was also verified that the addition of Pt and Pd as promoters increased the reducibility of nickel. Nickel dispersions measured by cyclohexane dehydrogenation showed small values, less than 5%. CO2-TPD results indicated that Ag-10%Ni/CeZrO2 catalyst presented the best redox properties among all catalysts. On the other hand, the samples 1.5%Ni/CeZrO2 and 10%Ni/Al2O3 presented smaller values of CO2 desorption, indicating low interaction between CO2 and the metal or CO2 and the support. The autothermal reforming of methane showed that the samples 10%Ni/CeZrO2 and Ag-10%Ni/CeZrO2 presented the higher methane conversion and better stability during the reaction. These two catalysts presented the highest values of CO2 and CO desorption during the CO2-TPD. 10%Ni/Al2O3 sample had the greatest initial activity. This catalyst presented the highest value of dispersion, indicating that, probably, the alumina favored the dispersion of nickel on its surface allowing better conditions for the dissociation of methane and the formation of H2 and CO. However, this catalyst did not show stability as the sample 10%Ni/CeZrO2, probably due to the fact that the alumina does not present redox properties as the CeZrO2 support.